2018
DOI: 10.1111/ijau.12134
|View full text |Cite
|
Sign up to set email alerts
|

What drives voluntary audit adoption in small German companies?

Abstract: The purpose of this study is to validate the drivers of voluntary audit in small companies identified in previous research and uncover additional determinants related to agency conflicts with owners. For our research we use the German institutional setting, documented in the literature as being very different from its Anglo-Saxon equivalent. Based on a random sample of 405 small companies responding to a postal questionnaire survey, we find that the proportion of owners not involved in management, the subsidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
(202 reference statements)
0
8
0
Order By: Relevance
“…However, the average rate of voluntary audits obtained by German private firms is only approximately 5%. Moreover, voluntarily audited firms are significantly larger and generally not under the control of an owner-manager but rather are the subsidiary of a stock corporation or controlled by a larger group of owners (Weik et al, 2018). While we cannot directly observe the audit status, we control for the voluntary disclosure of financial statements.…”
Section: Discussion and Possible Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the average rate of voluntary audits obtained by German private firms is only approximately 5%. Moreover, voluntarily audited firms are significantly larger and generally not under the control of an owner-manager but rather are the subsidiary of a stock corporation or controlled by a larger group of owners (Weik et al, 2018). While we cannot directly observe the audit status, we control for the voluntary disclosure of financial statements.…”
Section: Discussion and Possible Limitationsmentioning
confidence: 99%
“…Germany late-adopted the European Union regulation (Directive 2003/58/EC) regarding public disclosure of financial statements and the electronic filing of accounts (Grottke, Löffelmann, Haendel, & Späth, 2016). That it enacted the highest possible thresholds for mandatory financial statement disclosure and mandatory financial statement audits (Bernard, Burgstahler, & Kaya, 2018; Weik, Eierle, & Ojala, 2018) is also indicative of Germany’s reluctance.…”
mentioning
confidence: 99%
“…While countries like Denmark and Sweden require all companies to audit their accounts, UK and Germany are at the other extreme with high exemption limits with firms having to take their own decisions regarding audit based on costs and benefits of the same. Weik, A. et al [29] found that the proportion of firms opting for voluntary audits in Germany at 12% is far lower as compared to the proportion ranging between 26% -80% in other EU countries. In Malaysia, the study by Chan, W.…”
Section: Research On Demand For Voluntary Audit and Non-audit Servicesmentioning
confidence: 99%
“…Research suggests that users of small and medium enterprise (SME) financial reports differ across jurisdictions (Gassen, 2017). In addition, the need for audited financial reports varies depending on other aspects of the jurisdiction such as shareholder or stakeholder orientation (Barroso et al, 2018), management practices (Niemi et al, 2012; Weik et al, 2018) and entity characteristics (Collis, 2010; Dedman et al, 2014; Niemi et al, 2012; Weik et al, 2018). Research also highlights differences in voluntary audits across jurisdictions.…”
Section: Responses To Specific Questionsmentioning
confidence: 99%
“…Research also highlights differences in voluntary audits across jurisdictions. In a review of prior studies on this topic, Weik et al (2018) summarise that companies opting for voluntary audit are less common in Germany (12% of their sample) than in other countries analysed in prior literature (between 26% and 80% in Australia, Canada, Denmark, Finland and the UK). We believe, therefore, that globally enforced prohibitions are unlikely to be effective in meeting the unique needs of individual jurisdictions.…”
Section: Responses To Specific Questionsmentioning
confidence: 99%